A-187 Prior Concussion History and Recovery Time Following Sport-Related Concussion in High School Athletes. (17th August 2022) - Gaudet, Charles E; Iverson, Grant L; Zafonte, Ross; Berkner, Paul; Cook, Nathan E
Abstract: Objective: To examine whether adolescents with prior concussions take longer to return to school and/or sports following a subsequent sport-related concussion. Method: Injury surveillance data for 780 adolescents (M age=16.3, SD=1.3 years) were analyzed. Adolescents were divided into three groups: (a) no prior concussion history (69%; n=538), (b) history of one prior concussion (19.2%; n=150), and (c) history of two or more prior concussions (11.8%; n=92). We analyzed between-group differences in time to return to school and sports. Results: Groups did not differ in time to return to school (K-W: χ2(2)=0.95, p=.62; Log Rank: χ2 (2)=2.83, p=.24) or sports (K-W: χ2(2)=2.19, p=0.33; Log Rank: χ2 (2)=3.95, p=.14). However, a greater proportion of student athletes with two or more prior concussions had not returned to their sport at 28 days postinjury compared to those with no prior concussions (23.5% vs. 12.7%; OR=2.10, 95% CI 1.18-3.73). Of note, the two or more prior concussion group contained a higher proportion of adolescents with potential pre-injury risk factors for complicated recovery, namely, depression and migraines. Conclusions: Prior concussion history was not associated with longer time to return to school nor return to sport when examined as a continuous variable. However, at 28 days postinjury, a greater proportion of athletes with two or more prior concussions remained out of sports compared to those with no prior concussions.